Obstetric and perinatal consequences of childbirth in women with uterine leiomyoma - Siusiuka, V. H.; Kyryliuk, A.; Shevchenko, A. O.; Boguslavska, N. Yu.; Babinchuk, O. V.; Bachurina, O.; Сюсюка, Володимир Григорович; Шевченко, Анна Олександрівна; Богуславська, Наталія Юріївна; Бабінчук, Олена Василівна (My University, 2022)
The aim of the study - to assess the structure and frequency of obstetric and perinatal complications in pregnant women with uterine leiomyoma.